English-Pangutaran Sama dictionary - Walton, Janice (Summer Institute of Linguistics-Philippines, 1992)
A helpful reference for Pangutaran speaking students in their study of the English language. Contains synonyms, root words and affixes, sample sentences and an index of Pangutaran words.